Homologous or Heterologous COVID-19 Booster Regimens Significantly Impact Sero-Neutralization of SARS-CoV-2 Virus and Its Variants - Rome Buathong; Taweewun Hunsawong; Supaporn Wacharapluesadee; Suriya Guharat; Ratthapat Jirapipatt; Sasiprapa Ninwattana; Nattakarn Thippamom; Anusara Jitsatja; Anthony R. Jones; Kamonthip Rungrojchareonkit; Jindarat Lohachanakul; Rungarun Suthangkornkul; et al. (Vaccines, 2022)
We determined the levels of neutralizing antibodies against the SARS-CoV-2 ancestral strain, Delta and Omicron variants of concern (VOCs), in 125 healthcare workers who received CoronaVac as their primary vaccination and later received either a single ChAdOx1 or a combi-nation of two consecutive boosters using either two ChAdOx1 doses or a ChAdOx1 or BNT162b2 as the primary and second boosters, respectively, or two doses of BNT162b2. The titers 12 weeks after primary vaccination were inadequate to neutralize all strains. After a single ChAdOx1 booster, the levels of neutralization at Day 30 varied significantly, with only a small proportion of participants developing neutralizing titers against Omicron at Day 7 and 30. The two doses of ChAdOx1 as the booster induced the lowest activity. A combination ChAdOx1 and BNT162b2 induced greater neutralization than by two doses of ChAdOx1. Two doses of BNT162b2 as the booster had the maximal activity against Omicron VOC.